2022
DOI: 10.3389/fgwh.2022.835811
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatic Stress and Moral Injury in Maternity Care Providers: A Narrative and Exploratory Review

Abstract: IntroductionA significant percentage of maternity providers have experienced secondary traumatic stress following a traumatic birth. Previous studies identified it as an issue, but this literature review is 5–9 years old. In addition, the construct of moral injury has significantly increased our understanding of secondary trauma for military veterans. In the wake of COVID-19, this construct also applies to healthcare providers.ObjectivesThe present article updates these reviews and compares findings for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 46 publications
(104 reference statements)
0
21
0
Order By: Relevance
“…Restrictive regulation that limits midwifery practice authority has been associated with increased operative and preterm birth, which can lead to moral injury and secondary trauma for the medical team, which, in turn, is associated with attrition from employers or the workforce. 23,41 Furthermore, other state regulations that limit midwives' ability to practice, such as lack of Medicaid reimbursement parity with physicians, have been associated with fewer midwife births and also have the potential to affect the wellbeing of the workforce (eg, increasing the financial burden on a practice with CNMs). 42 Consequently, policymakers are encouraged to advocate for uniform and equitable state-level regulation of midwives as a strategy to strengthen the CNM/CM workforce and improve maternal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictive regulation that limits midwifery practice authority has been associated with increased operative and preterm birth, which can lead to moral injury and secondary trauma for the medical team, which, in turn, is associated with attrition from employers or the workforce. 23,41 Furthermore, other state regulations that limit midwives' ability to practice, such as lack of Medicaid reimbursement parity with physicians, have been associated with fewer midwife births and also have the potential to affect the wellbeing of the workforce (eg, increasing the financial burden on a practice with CNMs). 42 Consequently, policymakers are encouraged to advocate for uniform and equitable state-level regulation of midwives as a strategy to strengthen the CNM/CM workforce and improve maternal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 24 25 Specific investigation into the concept of moral injury in maternity care providers, especially in the context of trauma exposure, is limited. 26 However, the role of moral injury in predicting subsequent PTSD has been identified in contexts outside of maternity care. 27 This is a concept of particular relevance in the current COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Where there were issues about busyness and competing demands these may relate to the concept of moral injury, where professionals cannot deliver a service according to their expected standards 24 25. Specific investigation into the concept of moral injury in maternity care providers, especially in the context of trauma exposure, is limited 26. However, the role of moral injury in predicting subsequent PTSD has been identified in contexts outside of maternity care 27.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study of 907 women in the Netherlands found that 1.2 percent of women had birth-related PTSD, and 9 percent identified their births as traumatic 41 . Interestingly, maternity care providers also have lower rates of PTSD and secondary trauma in these same countries that use a midwifery model of care 42 .…”
Section: Incidencementioning
confidence: 99%